2020
DOI: 10.1007/s10570-020-03505-y
|View full text |Cite
|
Sign up to set email alerts
|

Superbase-based protic ionic liquids for cellulose filament spinning

Abstract: Lyocell fibers have received increased attention during the recent years. This is due to their high potential to satisfy the rising market demand for cellulose-based textiles in a sustainable way. Typically, this technology adopts a dry-jet wet spinning process, which offers regenerated cellulose fibers of excellent mechanical properties. Compared to the widely exploited viscose process, the lyocell technology fosters an eco-friendly process employing green direct solvents that can be fully recovered with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 70 publications
(88 reference statements)
1
32
0
Order By: Relevance
“…With an increase in the SR from 0 to 51, the tensile strength and elastic modulus of cellulose fibers increase significantly from 120.0 ± 9.2 MPa and 4.6 ± 0.6 GPa to 632.2 ± 32.0 MPa and 26.2 ± 1.8 GPa, respectively, possibly due to the increased crystallinity and enhanced oriented structure of the fiber. These results confirmed that solution stretching induced total molecular orientation and crystallization during the transition from solution to gel via coagulation, so dry fibers with a high SR could achieve high thermal stability and mechanical properties Figure c shows the strong correlation of the total molecular orientation factor, crystallinity, and mechanical properties.…”
Section: Resultssupporting
confidence: 65%
“…With an increase in the SR from 0 to 51, the tensile strength and elastic modulus of cellulose fibers increase significantly from 120.0 ± 9.2 MPa and 4.6 ± 0.6 GPa to 632.2 ± 32.0 MPa and 26.2 ± 1.8 GPa, respectively, possibly due to the increased crystallinity and enhanced oriented structure of the fiber. These results confirmed that solution stretching induced total molecular orientation and crystallization during the transition from solution to gel via coagulation, so dry fibers with a high SR could achieve high thermal stability and mechanical properties Figure c shows the strong correlation of the total molecular orientation factor, crystallinity, and mechanical properties.…”
Section: Resultssupporting
confidence: 65%
“…Only minor agglomerates were formed during spinning that are typical for a small-scale batch spinning process. The scanning electron microscopy images of the fibers, at DR 2 and 12, show a correlation of increased stretching on uniforming the fibers and eliminating surface irregularities (Elsayed et al 2021). The structural properties of the regenerated fibers were accessed by birefringence and WAXS measurements to estimate the crystalline and amorphous regions, summarized in Table 9.…”
Section: Lyocell Solvents For Cellulose Dissolution and Fibers Regenementioning
confidence: 99%
“…Ioncell fibers are lyocell type fibers produced via dry-jet wet spinning using a nontoxic and environmentally benign solvent, 1,5-diazabicyclo [4.3.0] non-5-ene acetate ([DBNH]­OAc), a nonimidazolium-based ionic liquid . Ioncell fibers exhibit outstanding fiber properties that are superior to cotton, viscose, and NMMO type lyocell fibers. …”
Section: Introductionmentioning
confidence: 99%